2019
DOI: 10.4274/eajem.galenos.2018.78941
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress and Related Factors Among Emergency Department Nurses

Abstract: Aim:The study determines moral distress and related factors among emergency nurses. Moral distress is one of the recurring issues in the nursing profession that has gained importance by creating changes in the health care system. Materials and Methods:An analytic-descriptive study was conducted, in which all 180 nurses working in emergency education and health centers in were included. Moral distress was measured by questionnaire. Data were analyzed using SPSS 17. Results:The findings showed that moral distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…A study by Jalali et al . showed that moral distress in emergency nurses is high,[ 56 ] which is in agreement with our results. In studies by Shafiei et al .…”
Section: Discussionsupporting
confidence: 93%
“…A study by Jalali et al . showed that moral distress in emergency nurses is high,[ 56 ] which is in agreement with our results. In studies by Shafiei et al .…”
Section: Discussionsupporting
confidence: 93%
“…high levels of tension and stress in the workplace were also factors affecting the level of PMC of the studied samples. The results of studies by Abbaszadeh et al and Jalali et al also showed high levels of tension and moral stress in the emergency and hospital wards, which has been considered as a factor affecting the level of courage and operation of personnel [38,39], but Fernandez-Parsons et al stated that the level of moral stress and tension in the emergency wards was low, which is contrary to the results in this study [40]. In 2017, Aminizadeh et al examined the relationship between nurses' PMC and moral stress in intensive care units.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported lower MD among nurses with higher age and greater work experience (14,17,18). However, a study found that MD had no significant relationship with age and work experience (19). A study also reported that nurses who worked in several hospitals had higher MD than those who worked in just one hospital (17).…”
Section: Personal Factorsmentioning
confidence: 99%